Manejo de solo e água e sua relação na qualidade e metabolismo da parede celular pós-colheita do tomate indústria - Martins, João Victor da Silva (2022)
The low availability of water and nutrients are limiting factors for agricultural production. The growing concern about water scarcity in recent years has aroused the interest of researchers in developing strategies that maximize the use of water and nutrients and maintain the final quality of the fruits. Tomatoes are the second most important vegetable in the world. Obtaining high yields and quality fruits for the industry involves the adoption of techniques that promote the increase and optimization of the water of the efficiency (WUE) and nutrients by the culture. Deficit regulated irrigation (DRI) is a technique that has been widely disseminated in order to reduce water use and increase the productivity of agricultural crops. However, the use of combined water and soil management, and its relationship with the final quality of tomato fruits destined for the industry, is still poorly understood. Therefore, the objective was to investigate the responses in the post-harvest quality of tomato industry, to the combined management strategies aimed at optimizing the use of water and nutrients by the plant. The experiment was in randomized blocks, with 4 replications in a split-plot scheme. Two irrigation frequencies (IF) (one and seven days) were implemented in the plots and three soil management models (conventional fertilization + limestone [FL]; conventional fertilization + gypsum + limestone [FGL]; conventional fertilization + gypsum + applied phosphorus in depth [FGLP]) were implemented in the subplots. The fruits were harvested 128 days after transplanting. Pulp firmness, soluble solids (SS), titratable acidity (TA), SS/TA ratio, dry matter (DM), reducing sugars (RS), amount of calcium (Ca2+) phenolic compounds (FC), total carotenoids (TC) were evaluated. The activities of the pectinolytic enzymes polygalacturonase (PG) and pectinmethylesterase (PME) were also determined. Soil management with FGL and IF of seven days provided higher SS and RS content in the fruits. The SS/TA ratio was higher in the fruits submitted to IF for seven days, with no difference between the types of managements. Fruit firmness was higher with FGL and IF of seven days and had an inverse relationship with the activity of PG and PME enzymes. The percentage of DM was higher in fruits managed with FL and FGL plus IF of seven days. The amount of calcium (Ca2+) in tomato fruits was lower only in the treatment composed of FL and IF of seven days. The phenolic compounds and total carotenoids were higher in the FGL treatment and in all the seven-day IF managements. The combined water and soil management strategies promoted an increase in post-harvest quality of the tomato industry. The FGL and IF treatment of seven days positively influenced the total soluble solids, reducing sugars, SS/TA ratio, firmness, dry matter, phenolic compounds and total carotenoids in tomato